The Investıgatıon Of The Profıle On The Patıents Wıth Hypodontıa, Havıng Bılateral Congenıtal Absence Of Maxıllary Lateral Incısors - Neslihan Üçüncü (Galenos Yayinevi, 1990)
The causes of absence of maxillary lateral incisors are said to be the environmental factors such as radiation, trauma, tumors and systemic disease or the genetic factors. The jaw development is effected as a result of the absence of teeth. It is also known that the form of the jaws and dentoalveolar structures are effective on the profile. In this study, the effect of the bilateral absence of maxillary lateral incisors on the soft tissue profile has been investigated by utilizing different analysis. A statistically significant retrusion in the upper jaw of the individuals with hypodontia is observed when compared with the individuals with normal occlusion and all the permanent teeth developing. There were no other significant change found, regarding the other parameters.